Correlation of CagA-Positive Strains of Helicobacter pylori with Topographic Distribution and Chronic Gastritis Grading - I Gede Arinton; Pugud Samudro; Soewignjo Soemohardjo; Sarjadi Sarjadi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
Background: CagA gene is a marker for the presence of Cag pathogenicity island. CagA-positive strains of Helicobacter pylori can identify individuals who have higher risk of developing gastrointestinal diseases. Aim: To discover the correlation of CagA status of Helicobacter pylori with topographic localization of Helicobacter pylori and chronic gastritis grading. Methods: Gastric biopsy specimens were taken from 104 patients. The specimens were obtained from gastric antrum, corpus and incisures for histological and polymerase chain reaction (PCR) studies. The histological chronic gastritis was assessed semi-quantitatively (grades 0-3). The PCR was used for detecting Helicobacter pylori genes and CagA strain. Topographic localization of Helicobacter pylori was classified as gastric antrum and corpus. Results: There were 33 (86.8%) CagA-positive strains of 38 patients with Helicobacter pylori-positive genes. There were no significant differences between topographic localization of Helicobacter pylori - either in the gastric antrum (rho = 0.14, p = 0.40) nor in the corpus (rho = 0.27, p =0.10) and the CagA status of Helicobacter pylori. Conclusion: CagA gene status of Helicobacter pylori does not determine chronic gastritis grading and gastric topographic localization. Keywords: chronic gastritis, cagA gene, Helicobacter pylori, gastric antrum, gastric corpus.